PENARIKHAN RADIOKARBON DALAM PENENTUAN AKTIVITAS TEKTONIK KUARTER DI SEPANJANG ALIRAN SUNGAI OPAK DAN PANTAI SAMAS, YOGYAKARTA - Siregar, Darwin A; Soehaimi, Asdani (Pusat Survei Geologi, 2009)
The Samas beach ridges and river terraces of Opak, Progo, Oyo and Berbah in the research area were formed by the neotectonic activities since ± 7000 years ago until Recent. Materials for Radiocarbon dating consists of mollusc and organic clay found in the beach ridge and river terrace deposits. The oldest Samas beach sand is 1980 ± 120 years BP and Opak River terrace at Berbah is 6950 ± 300 years BP. Meanwhile, the Oyo River terrace at Siluk is 2640 ± 100 years BP and Opak River terrace at Karang is 1220 ± 120 years BP. The dynamic neotectonic activities of Samas beach are represented by the uplifting and shifting of the coast line, meanwhile at Berbah, Siluk and Karang are indicated by uplifting end shifting of the river base level. These dynamic activities were caused by the regional tectonic activity related to subduction in the south of Java island and the local tectonic activity along the Opak fault zone. Keywords : Dynamic of beach sand, river terrace, elevation and radio carbon dating